Medicine as culture illness, disease, and the body - Lupton, Deborah (Sage, 2012)
Provides a broad overview of the ay medicine is experienced, percieved and socially constructed in western societies. Drawing on the sociology of health and illness, the author directs readers to an understanding of medicine, health care, illness and disease from a socio-cultural perspective.